Advances on computational intelligence in energy : the applications of nature-inspired metaheuristic algorithms in energy /: the applications of nature-inspired metaheuristic algorithms in energy. ([2019]) - Herawan, Tutut; Chiroma, Haruna; Abawajy, Jemal H
No abstract available